The effects of aerobic gymnastics training on performance-related variables in an elite athlete: a 2-year follow-up study - Kyselovičová, Oľga; Zemková, Erika (Frontiers in Physiology, 2024)
This study investigates individual performance adaptations on two years of training between European Aerobics Championships. An elite, 22-year-old aerobic gymnast performed postural coordination test, Y-Balance test, countermovement jumps, 60 s test of repeated jumps, an isokinetic leg muscle strength test, and the Wingate test. Postural stability and flexibility improved in terms of increased distance achieved in the Y-Balance test in the anterior (by 6.3%), posteromedial (by 2%), and posterolateral (by 4.8%) directions. Lower limb muscular endurance also increased, which can be corroborated by a reduced fatigue index in the 60 s test of repeated jumps (from 42% to 27% after the 1 st and to 22% after the 2 nd year of training). In addition, mean power increased during dominant (at 60°/s by 23.2% and 180°/s by 18.5%) and non-dominant leg extension (at 180°/s by 4.9% and 300°/s by 15.5%), plus dominant leg flexion (at 60°/s by 2.0% and 300°/s by 6.9%). Similarly, peak torque/body weight ratio increased during dominant (at 60°/s by 24.9%, 180°/s by 11.5%, and 300°/s by 2.1%) and nondominant leg extension (at 60°/s by 0.5% and 300°/s by 6.4%), plus dominant leg flexion (at 60°/s by 1.7% and 300°/s by 5.4%). However, two years of training failed to show any significant improvements in the explosive power of lower limbs and anaerobic performance. These findings indicate that general aerobic gymnastic training without any specific inputs leads to performance adaptation, namely in abilities closely related to competition routine (dynamic balance and strength endurance of lower limbs).